Stay with me - Bennett, Jules (Bennett, Jules. Return to Haven., 2018)
At eighteen, Olivia Daniels left Haven behind and never looked back. Doggedly climbing the corporate ladder, she<U+2019>s finally nearing the top when her father dies<U+2014>leaving her part-owner of the run-down airport that was his first love. It<U+2019>s a complication Olivia intends to wrap up quickly<U+2014>buying out her co-owner and selling the land. Good thing her childhood best friends are with her for moral support. Because one look at her new partner is proof that her tidy plan has hit turbulence . . . Jackson Morgan practically grew up in Haven<U+2019>s airport, and no one could have been a better mentor than Olivia<U+2019>s dad. Flight is in Jackson<U+2019>s blood, but his roots are firmly planted, and there<U+2019>s no way he<U+2019>s giving up the airport<U+2014>not even for sassy, headstrong Olivia, his childhood crush. Coming to an agreement won<U+2019>t be easy, especially when the attraction between them soars to new heights every day. Love definitely wasn<U+2019>t on the itinerary, but is it enough to keep them together for a lifetime trip? . . .